Implementation of COVID-19 Vaccination in Makwanpur District of Nepal: Readiness and Challenges of a Restructured Health System - Aashma Dahal; Neeti Bhat; Bishal Poudel; Safal Poudel; Roshan Shrestha (COVID, 2025)
This research study explores the readiness, strengths, and challenges of the district health system and local bodies during Nepal’s COVID-19 vaccination program. The primary aim of this study is to identify gaps in the current health system and provide actionable insights for the effective implementation and management of large-scale health programs in the future. A qualitative approach was employed, gathering perspectives of key stakeholders through twelve key informant interviews of stakeholders involved in the planning, management, and execution of the vaccination program in Makwanpur district, the district with the administrative headquarters of Bagmati Province. The study was conducted in the context of Nepal’s transitioning health system following federalization. The qualitative data were analyzed using thematic analysis, guided by the VIRAT2.0 framework for vaccine readiness provided by the WHO. Seven domains from the framework were used to assess readiness and challenges faced by the newly formed health system. The challenges identified by key informants included insufficient logistics and supply chain management, poor coordination between local and higher levels of government, limited awareness about vaccination among the public, vaccine hesitancy, and lack of a robust system for data management and reporting. These findings highlight critical areas for improvement and can be useful evidence to inform the design and implementation of future health programs and policies.